2004
DOI: 10.1002/hed.20103
|View full text |Cite
|
Sign up to set email alerts
|

Same-day discharge after total thyroidectomy: The value of 6-hour serum parathyroid hormone and calcium levels

Abstract: Background. The purpose of this study was to determine whether patients who undergo total thyroidectomy will have postoperative hypocalcemia develop when they reach the critical 6-hour serum levels defined as parathyroid hormone (PTH) z28 ng/L and simultaneous corrected calcium z2.14 mmol/L.Methods. This was a prospective study involving 70 consecutive total thyroidectomy patients. There were 51 women and 19 men involved in the study. The mean age was 49.3 years (range, 21 -76 years). Patients who had completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 19 publications
5
93
0
2
Order By: Relevance
“…In our study, the rate of the patients with laboratory transient hypocalcemia (27%) and those with clinically transient hypocalcemia (23%) was in the interval of 6.2-68%, which was simi-lar to that reported in the literature. 2,3,14,[22][23][24][25][26] In the study by Wilson et al, in which the definitions of laboratory and clinical hypocalcemia are similar to the definitions in our study, 68% of patients were diagnosed with laboratory transient hypocalcemia and 36% of patients had symptoms of hypocalcemia. 3 They defined hypomagnesemia as serum concentration of magnesium lower than 0.7 mmol/L and the same definition was used in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, the rate of the patients with laboratory transient hypocalcemia (27%) and those with clinically transient hypocalcemia (23%) was in the interval of 6.2-68%, which was simi-lar to that reported in the literature. 2,3,14,[22][23][24][25][26] In the study by Wilson et al, in which the definitions of laboratory and clinical hypocalcemia are similar to the definitions in our study, 68% of patients were diagnosed with laboratory transient hypocalcemia and 36% of patients had symptoms of hypocalcemia. 3 They defined hypomagnesemia as serum concentration of magnesium lower than 0.7 mmol/L and the same definition was used in our study.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of an incidentally detected parathyroid tissue in histologic material (10.5%) is comparable to that in other similar studies, yet still at lower level of the incidence range reported in the literature (9-15%). [19][20][21] The incidence of transient hypocalcemia after thyroidectomy reported in the literature differs from study to study 14,[22][23][24][25][26] due to the differences in the reference calcium values of laboratory test, definitions of laboratory transient hypocalcemia and clinical transient hypocalcemia. In our study, the rate of the patients with laboratory transient hypocalcemia (27%) and those with clinically transient hypocalcemia (23%) was in the interval of 6.2-68%, which was simi-lar to that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (3)(4)(5)(6) consider early postoperative (24-hour) serum calcium levels and intraoperative identification of parathyroid glands to be important predictive factors. Others (7)(8)(9) have instead suggested combining intact parathyroid hormone (PTH) and serum calcium measurements, arguing that PTH and serum calcium monitoring after the first postoperative hour would allow reliable prediction of postoperative hypocalcemia. Some authors (10)(11)(12) recommend quick PTH assay as a means of predicting postoperative parathyroid function, although others (13) found no overall significant difference in the capacity of intraoperative PTH levels, versus early postoperative serum calcium levels (day 1), to predict long-term hypoparathyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that low serum iPTH levels during postoperative period is a predictive factor for hypocalcemia (11,12,14,20,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%